Serum cadmium levels in a sample of blood donors in the Western Amazon, Brazil, 2010-2011 - Andre Ricardo Maia da Costa de Faro; Wagner de Jesus Pinto; Aldo Pacheco Ferreira; Fernando Barbosa Junior; Vanessa Cristina de Oliveira Souza; Denys Eiti Fujimoto; Rosalina Jorge Koifman; Sergio Koifman (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2014)
A cross-sectional study was conducted to determine the distribution of serum cadmium (Cd) levels in blood donors in Rio Branco, Acre State, Brazil. Blood samples were obtained from 922 volunteer blood donors from 18 to 65 years of age at the Hemoacre blood center in 2010-2011. Mean serum Cd was 0.37µg/L (95%CI: 0.33-0.41). Increased serum Cd was associated with lower schooling; individuals with less than five years of schooling showed a mean Cd of 0.61µg/L (95%CI: 0.34-0.89), compared to 0.34µg/L (95%CI: 0.28-0.40) among those with more than nine years of schooling. Mean serum Cd was three times higher among smokers. Smoking showed a positive association with Cd level, with an OR of 12.36 (95%CI: 7.70-19.84). Meanwhile, serum Cd was lower among individuals that regularly drank tea, as compared to non-tea drinkers. Serum Cd levels were mostly below the reference value (88.3% of participants). Mean serum Cd in the current study indicates that in general the population studied here is not exposed to worrisome Cd levels.